An exploratory study of AI participants' views on using AI in business hotels - Leong, Kelvin; Sung, Anna (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study presents a novel approach to exploring the viewpoints of AI bots regarding the utilization of AI in business hotels using thematic analysis. Interviews were conducted with AI bots serving as the subjects. The rationale for this approach is that AI bots have undergone extensive training using a wide range of data from different internet sources. Therefore, having an interview with an AI bot can be viewed as an interaction with an entity that embodies collective viewpoints and information derived from the internet. The study has unearthed crucial themes that offer invaluable insights to industry participants and policymakers, contributing to the expansion of existing literature by generating novel knowledge and fostering a comprehensive understanding. The pioneering approach of incorporating AI bots as participants in interviews opens up fresh avenues for future research endeavours and engenders discussions and debates concerning the use of AI bots as participants.